Common factors in prices, order flows, and liquidity - Hasbrouck, J (Journal of Financial Economics, 2001)
How important are cross-stock common factors in the price discovery/liquidity provision process in equity markets? We investigate two aspects of this question for the 30 Dow stocks. First, using principal components and canonical correlation analyses we find that both returns and order flows are characterized by common factors. Commonality in the order flows explains roughly two-thirds of the commonality in returns. Second, we examine variation and common covariation in various liquidity proxies and market depth (trade impact) coefficients. Liquidity proxies such as the bid–ask spread and bid–ask quote sizes help explain time variation in trade impacts. The common factors in these liquidity proxies are, however, relatively small.